FENOMENA MEME QS. AL-NISA AYAT 34 TENTANG OTORITAS KEPEMIMPINAN DALAM KELUARGA DI MEDIA SOSIAL - Hasiah; Sawaluddin Siregar (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2024)
This article aims to communicate about the QS meme phenomenon. al-Nisa verse 34 relates to leadership authority in the family, as spread on social media. The aim is to look further into the trend of QS consumption patterns. al-Nisa verse 34 of each existing meme and to identify the motive behind the creation of the meme. This type of research is library research using a constructivist approach. The results of this research show that; First, there are at least two tendencies of QS memes. al-nisa verse 34 on social media, namely; memes that start from the textual meaning paradigm and memes that start from the contextual meaning paradigm. Second, the creation of textualist memes mostly only starts from the meaning of the translation of the verse and there is only one meme that has an interpretive reference, only taking classical interpretations and turning a blind eye to quoting the interpretations of contemporary scholars. Meanwhile, contextual memes are created as a result of elaboration between the interpretations of classical and contemporary scholars. Third, the dominance of textual memes is far greater in quantity compared to contextual memes that are scattered on social media, so this has the implication of giving the impression that Islamic teachings seem to discredit the role of women in the family